(untitled) (Bangladesh Rice Journal, 2016)
Tegra practice (healthy seedling, mechanical transplanting, herbicide application and advisory services), as a new concept in commercial rice cultivation, needs to be evaluated with farmers practices in our country. This study was conducted in the farmers field during Aman 2013 and Boro 2013-14 seasons in Bogra district. In each season, six farmers within one kilometer radius were selected to conduct this study. Randomized complete block design (RCBD) with two treatments namely farmers practices (FP) and Tegra practices (TP) were used in the experiment. Self-propelled four rows walking-type rice transplanter was used to transplant seedling in TP. Seedlings were raised in plastic tray to use in mechanical transplanter. The mat seedlings were ready to transplant when attained 3-4 leaves and 10-12 cm height. Mechanical transplanting found faster than manual transplanting. Missing/floating hill observed insignificant in mechanically transplanted field. Fuel consumption of mechanical transplanter obtained 4.5 L/ha. Tender aged seedling was used in TP and seedling age was higher in FP than TP. Plant height followed the similar trend in both the practices. Tillering ability obtained the highest in TP than FP. TP produced significantly higher (14-23%) grain yield in both seasons. The total cost of production, gross return, gross margin and BCR obtained the highest in TP. BCR showed 5-13% higher in TP than FP in both the seasons due to higher grain and straw yield. The economic analysis clearly revealed the profitability of TP over FP in both the seasons. Bangladesh Rice j. 2016, 20(1): 33-43